KEPENTINGAN INDONESIA MEMBERLAKUKAN KEBIJAKAN BEA MASUK TINDAKAN PENGAMANAN (BMTP) PERDAGANGAN TERHADAP IMPOR PRODUK BAJA GALVALUME (STUDI KASUS: IMPOR BAJA INDONESIA VIETNAM) - Agustian "; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study explains that there is a surge in imports of Indonesian galvalume steel products from several market shares in the main import origin countries. The increase occurred in 2012 when compared to 2008 it was noted that the most galvalume steel products were imported from Vietnam with a share of 60.04%. The increase in market share for Vietnam was 11.45%. With the surge in imports, there is a threat of serious losses experienced by the Indonesian galvalume steel industry. Therefore, Indonesia enforces a policy of protectionism against imports of galvalume steel. The author discusses the interests of Indonesia in imposing a Safeguard Measures Import Duty (BMTP) Policy on the Import of Galvalume Steel Products (case study: Indonesia-Vietnam Steel Imports).          The perspective used in this study is Markantilism and uses the level of analysis of the nation state. This research uses the theory of Protectionism that is able to explain the country's strategy in protecting the domestic galvalume steel industry from the threat of imported steel and overcome the problem by enacting the Safeguards Policy.          This research shows that the Indonesian government's Safeguards policy has a in protecting the domestic galvalume steel industry from the flood of imported steel that causes a serious threat of harm to industries that produce similar goods. Keywords: BMTP, National Interest, Galvalume, Security Measures, Protectionism.